2019
DOI: 10.1504/ijsmm.2019.099782
|View full text |Cite
|
Sign up to set email alerts
|

Sport pro = Twitter pro - How soccer stars use Twitter at the height of their career

Abstract: This paper examines the usage of Twitter by professional soccer clubs and players in the context of a major sporting event. The study focuses on the UEFA Champions League Final in 2013, which featured two German football clubs. Nearly 300 tweets were coded via eight variables (author, content, date, language, media, mood, person and team). The results reveal considerable differences between the levels of activity and the players' Twitter performance. The clubs accompanied the season highlight in a communicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…Sports-related social media research has mostly engaged with questions about how individuals, clubs and organisations strategically use social media as a communicative branding instrument (Geurin-Eagleman and Burch 2016; Grimmer and Clavio 2019; Kautz, Schaffrath, and Gang 2020). In a review of 70 sport management articles, Filo, Lock, and Karg (2015) found that research tended to focus on the operational and user-focused dimensions of how this communication ultimately aimed to cultivate relations between individuals and brands.…”
Section: Previous Research On Masculinities In Sports and (Social) Mediamentioning
confidence: 99%
“…Sports-related social media research has mostly engaged with questions about how individuals, clubs and organisations strategically use social media as a communicative branding instrument (Geurin-Eagleman and Burch 2016; Grimmer and Clavio 2019; Kautz, Schaffrath, and Gang 2020). In a review of 70 sport management articles, Filo, Lock, and Karg (2015) found that research tended to focus on the operational and user-focused dimensions of how this communication ultimately aimed to cultivate relations between individuals and brands.…”
Section: Previous Research On Masculinities In Sports and (Social) Mediamentioning
confidence: 99%
“…Relationship marketing with customers and fans using social media platforms (Abeza et al , 2019; Achen, 2019) and success factors of marketing communication via social media (Billings et al , 2019; Courthouts et al , 2019; Laurell and Söderman, 2018; Teo et al , 2019) were examined. Social media research addressing brand management mainly investigated how sports organizations and athletes build their brands and develop their brand images using social media (Anagnostopoulos et al , 2018; Grimmer and Clavio, 2019; Hayes et al , 2020; Hayes and Blaszka, 2018; Na et al , 2020; Srivardhana, 2019; Thompson et al , 2018). Social media research has also explored platform activity to analyze and control ticket prices in secondary markets (O'Hallarn et al , 2018b).…”
Section: Literature Review: Digital Transformation In Sport Management Researchmentioning
confidence: 99%
“…Internet y los nuevos medios sociales posibilitan el flujo multidireccional de mensajes y mayores posibilidades de selección, expresión y comunicación (Sotelo, 2012, p. 218). Y la crisis económica, como en el caso español, también ha afectado a los clubes profesionales de fútbol, obligándoles a reinventarse en muchos ámbitos, teniendo mucha importancia en este contexto la gestión de la comunicación que realizan estas entidades en el medio internet, especialmente en las principales redes sociales (Grimmer & Clavio, 2019).…”
Section: Clubes De Fútbol Y Redes Socialesunclassified